(untitled) (Novateur Publications, 2023)
In this monograph, it is based on the formation of important professional qualities of professional specialists, the composition of knowledge, skills and qualifications specific to the profession of a psychologist. For this, first of all, it is important to understand the essence of the chosen profession and to develop its own important characteristics. Studying what the composition of important professional qualities is and what psychological factors are associated with their formation determines that the problem is relevant for today. In particular, the socio-psychological portrait of a psychologist is dominated by the factor of communicative, intellectual, emotional and self-regulation of the individual. This monograph aims to reveal exactly such qualities in expert psychologists.